Prevention and Law Enforcement of Criminal Acts of Corruption Causing State Financial Losses - Yanto M.P. Ekon; Melkianus Ndaomanu; Yohana Lince Aleng; Ira D. Mangililo; Ellon Belwan Cornelium Mau (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
Corruption crimes causing state financial losses in East Nusa Tenggara Province (NTT) continue to increase. As an archipelagic province, all corruption cases across 21 districts and 1 city must be tried at the Corruption Crime Court in Kupang, requiring substantial state operational costs. This normative legal research, employing descriptive and prescriptive methods, analyzes court decisions from the Kupang Corruption Court to examine prevention strategies and selective law enforcement mechanisms. The findings reveal that most corruption cases stem from government procurement, particularly construction services. Critical acts include volume shortfalls, work not conforming to specifications, building failures, and failure to disburse maintenance guarantees. The research demonstrates that law enforcement often increases state financial losses when the proven loss is smaller than the operational budget (ranging from IDR 491–492 million per case) or when defendants are acquitted, wasting state funds. Between 2020–2024, corruption caseloads fluctuated between 49–92 cases annually, confirming that punitive-centric enforcement alone is ineffective. This study proposes: (1) involving competent university experts in procurement processes to verify materials, volumes, and specifications before fund disbursement; (2) amending legislation to limit Corruption Court jurisdiction to cases involving minimum losses of IDR 1 billion, harmonizing with KPK authority; and (3) adopting selective enforcement prioritizing state financial recovery over imprisonment, especially for de minimis losses. Building failures should be resolved under Construction Services Law (civil remedies), not automatically prosecuted as corruption. Effective corruption enforcement should be measured by recovered state assets, not solely by conviction rates.